Zur Frage des DaF-Unterrichts an der staatlichen Buketov-Universität Karaganda: Praktikum, Erfahrungen, Empfehlungen - Timann, Yu.; Tleuzhanova, G.K.; Shunkeyeva, S.A. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
In the article actualized the questions of the foreign language education, particularly, teaching German language as foreign language in the higher education system. Buketov Karaganda State University comes forward with the basis of the research, where the first time educational practice of the Master's Degree students from the Europe was organized as part of the academic mobility. Realization of the academic mobility, one of the most important characteristics of the Bologna process encouraged realization of the collective researches in area of linguodidactics, acquisition of new knowledge and the exchange of experience.
Неміс тілін шетел тілі ретінде оқыту мəселесі: Е.А.Бөкетов атындағы ҚарМУ тəжірибесінен
К вопросу преподавания немецкого языка как иностранного: из опыта КарГУ им. Е.А.Букетова
Keywords: die Fremdsprachen; der Bologna-Prozess; die Auslandsmobilität; das Bildungssystem; das Auslandssemester; der Praktikant; die internationale Zusammenarbeit; die Realisierung; das Niveau; die außercurriculäre Tätigkeit